Health-care-associated bloodstream and urinary tract infections in a network of hospitals in India: a multicentre, hospital-based, prospective surveillance study. Issue 9 (September 2022) - Mathur, Purva; Malpiedi, Paul; Walia, Kamini; Srikantiah, Padmini; Gupta, Sunil; Lohiya, Ayush; Chakrabarti, Arunaloke; Ray, Pallab; Biswal, Manisha; Taneja, Neelam; Rupali, Priscilla; Balaji, Veeraraghavan; et al.
Summary: Background: Health-care-associated infections (HAIs) cause significant morbidity and mortality globally, including in low-income and middle-income countries (LMICs). Networks of hospitals implementing standardised HAI surveillance can provide valuable data on HAI burden, and identify and monitor HAI prevention gaps. Hospitals in many LMICs use HAI case definitions developed for higher-resourced settings, which require human resources and laboratory and imaging tests that are often not available. Methods: A network of 26 tertiary-level hospitals in India was created to implement HAI surveillance and prevention activities. Existing HAI case definitions were modified to facilitate standardised, resource-appropriate surveillance across hospitals. Hospitals identified health-care-associated bloodstream infections and urinary tract infections (UTIs) and reported clinical and microbiological data to the network for analysis. Findings: 26 network hospitals reported 2622 health-care-associated bloodstream infections and 737 health-care-associated UTIs from 89 intensive care units (ICUs) between May 1, 2017, and Oct 31, 2018. Central line-associated bloodstream infection rates were highest in neonatal ICUs (>20 per 1000 central line days). Catheter-associated UTI rates were highest in paediatric medical ICUs (4·5 per 1000 urinary catheter days). Klebsiella spp (24·8%) were the most frequent organism in bloodstream infections and Candida spp (29·4%) in UTIs. Carbapenem resistance was common in Gram-negative infections, occurring in 72% of bloodstream infections and 76% of UTIs caused by Klebsiella spp, 77% of bloodstream infections and 76% of UTIs caused by Acinetobacter spp, and 64% of bloodstream infections and 72% of UTIs caused by Pseudomonas spp. Interpretation: The first standardised HAI surveillance network in India has succeeded in implementing locally adapted and context-appropriate protocols consistently across hospitals and has been able to identify a large number of HAIs. Network data show high HAI and antimicrobial resistance rates in tertiary hospitals, showing the importance of implementing multimodal HAI prevention and antimicrobial resistance containment strategies. Funding: US Centers for Disease Control and Prevention cooperative agreement with All India Institute of Medical Sciences, New Delhi. Translation: For the Hindi translation of the abstract see Supplementary Materials section.